Genome-wide identification and expression analysis of the cryptochromes reveal the CsCRY1 role under low-light-stress in cucumber - Cao, Haishun; Wang, Rui; Zhao, Junhong; Shi, Liangliang; Huang, Yuan; Wu, Tingquan; Zhang, Changyuan (Frontiers in Plant Science, 2024)
Introduction Low-light-stress is a common meteorological disaster that can result in slender seedlings. The photoreceptors play a crucial role in perceiving and regulating plants' tolerance to low-light-stress. However, the low-light-stress tolerance of cucumber has not been effectively evaluated, and the functions of these photoreceptor genes in cucumber, particularly under low-light-stress conditions, are not clear. Methods Herein, we evaluated the growth characteristics of cucumber seedlings under various LED light treatment. The low-light-stress tolerant cucumber CR and intolerant cucumber CR were used as plant materials for gene expression analysis, and then the function of CsCRY1 was analyzed. Results The results revealed that light treatment below 40 μmol m-2 s-1 can quickly and effectively induce low-light-stress response. Then, cucumber CR exhibited remarkable tolerance to low-light-stress was screened. Moreover, a total of 11 photoreceptor genes were identified and evaluated. Among them, the cryptochrome 1 (CRY1) had the highest expression level and was only induced in the low-light sensitive cucumber CS. The transcript CsaV3_3G047490.1 is predicted to encode a previously unknown CsCRY1 protein, which lacks 70 amino acids at its C-terminus due to alternative 5′ splice sites within the final intron of the CsCRY1 gene. Discussion CRY1 is a crucial photoreceptor that plays pivotal roles in regulating plants' tolerance to low-light stress. In this study, we discovered that alternative splicing of CsCRY1 generates multiple transcripts encoding distinct CsCRY1 protein variants, providing valuable insights for future exploration and utilization of CsCRY1 in cucumber.